11, 12-Diacetyl-carnosol Protects SH-SY5Y Cells from Hydrogen Peroxide Damage through the Nrf2/HO-1 Pathway. (17th May 2022) - Luo, Qingyi; Hu, Weiyan; Yu, Haofei; Zhang, Rongping; Chen, Xinglong
Abstract : Background . Oxidative stress-induced neurotoxicity plays a key role in Alzheimer's disease (AD). 11, 12-Diacetyl-carnosol (NO.20), an acetylated derivative of carnosol extracted from rosemary, displays a high antioxidative effect in vitro. Purpose . We investigated the neuroprotective effect of NO.20 on H2 O2 -induced neurotoxicity in human neuroblastoma SH-SY5Y cells and its possible mechanism. Results . We found that NO.20 pretreatment (1 μ M for 1 h) had cytoprotective effects and weakened H2 O2 -induced damage in SH-SY5Y cells by reducing viability loss, apoptotic rate, and reactive oxygen species production. In addition, NO.20 inhibited H2 O2 -induced mitochondrial dysfunctions: it alleviated mitochondrial membrane potential loss and cytochrome c release, decreased the Bax/Bcl-2 ratio, and reduced caspase-3 expression. NO.20 also downregulated malondialdehyde and upregulated glutathione. Furthermore, NO.20 pretreatment caused the nuclear translocation of the transcription factor NF-E2-related factor 2 (Nrf2), increasing heme oxygenase-1 (HO-1) expression in SH-SY5Y cells. Notably, we found that silencing Nrf2 using small interfering RNA (siRNA) suppressed the NO.20-induced HO-1 expression and abolished the neuroprotective effect of NO.20. Conclusion . These results demonstrate that NO.20 protects SH-SY5Y cells from H2 O2 -induced neurotoxicity by activating the Nrf2/HO-1 pathway. Thus, the neuroprotective and antioxidative stress effects of NO.20 may make it a promising neuroprotective compound for AD treatment.